THE EFFICACY OF DORAMECTIN FOR TREATMENT OF Ancylostomiasis IN DOGS - Ida Tjahajati (Jurnal Sain Veteriner, 2000)
A study was done to evaluate the efficacy of doramectin injection for Ancylostomiasis treatment in 10 dogs. All of the dogs were heavily and naturally infected with Ancylostoma Sp. the heavy infection criterion (25 egg per gram) was based on the flotation method. At the beginning of the study the dogs were injected doramection subcutaneously (200 ,wg/kg of body weight). The pathogenesis of the disease was observd through the clinical sign and feses examination during 2 weeks after treatment. Dogs were considered recovery when they have a good response to the treatment and clinically showed normal of apetite, no sign of diarrhea and no egg was found laboratorically. Results of the study showed that all of the dogs had positive response to the treatment and therefore it can be concluded that doramectin effective against Ancylostoma Sp. in dogs.